The Influence of Industrial Work Experience and the Use of Social Media on the Entrepreneurial Interest of Class XII Marketing Students - Sitanggang, Dormauli Berlyanti; Rahmadana, Muhammad Fitri (Economic: Journal Economic and Business, 2025)
This study aims to analyze the influence of industrial work practice experience and social media utilization on the entrepreneurial interest of Grade XII Marketing students at SMK Negeri 1 Medan. A quantitative approach with an ex post facto method was employed. The sample consisted of 64 students selected through a census technique. Data were collected using a questionnaire and analyzed using multiple linear regression with SPSS version 27. The results show that industrial work practice experience has a positive and significant effect on entrepreneurial interest (tcount = 5.751; sig. = 0.000), as does social media utilization (tcount = 3.171; sig. = 0.002). Simultaneously, both variables significantly influence entrepreneurial interest (Fcount = 36.285; sig. = 0.000). The coefficient of determination (R²) is 0.543, indicating that both independent variables contribute 54.3% to the variation in students’ entrepreneurial interest. These findings underscore the importance of hands-on experience and the strategic use of digital technology in fostering entrepreneurial spirit among vocational school students.